Analisis Pengaruh Eco-Innovation Terhadap Sustainability Performance Dengan Innovative Performance Sebagai Variabel Mediasi - Muchlisin, Muchlisin (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2025)
Sustainable business is an important issue facing Micro, Small and Medium Enterprises (MSMEs). This research aims to examine eco-innovation which influences sustainability performance by triggering innovative performance capabilities as resource-based mediation. This research was conducted in Cilacap Regency, Central Java, Indonesia with a population of 106 MSME respondents who produce goods in the craft industry sector. The results show that eco-organization has no effect on innovative performance. However, the role of eco-process and eco-product has a very significant influence on innovative performance. while innovative performance has a positive influence with high significance on sustainability performance. This shows that the application of various innovations, both product and process innovation, has an important role in maintaining MSME businesses in the long term.